Inference of population structure of purebred dairy and beef cattle using high-density genotype data. (22nd June 2016) - Kelleher, M. M.; Berry, D. P.; Kearney, J. F.; McParland, S.; Buckley, F.; Purfield, D. C.
Abstract : Information on the genetic diversity and population structure of cattle breeds is useful when deciding the most optimal, for example, crossbreeding strategies to improve phenotypic performance by exploiting heterosis. The present study investigated the genetic diversity and population structure of the most prominent dairy and beef breeds used in Ireland. Illumina high-density genotypes (777 962 single nucleotide polymorphisms; SNPs) were available on 4623 purebred bulls from nine breeds; Angus ( n =430), Belgian Blue ( n =298), Charolais ( n =893), Hereford ( n =327), Holstein-Friesian ( n =1261), Jersey ( n =75), Limousin ( n =943), Montbéliarde ( n =33) and Simmental ( n =363). Principal component analysis revealed that Angus, Hereford, and Jersey formed non-overlapping clusters, representing distinct populations. In contrast, overlapping clusters suggested geographical proximity of origin and genetic similarity between Limousin, Simmental and Montbéliarde and to a lesser extent between Holstein, Friesian and Belgian Blue. The observed SNP heterozygosity averaged across all loci was 0.379. The Belgian Blue had the greatest mean observed heterozygosity (HO =0.389) among individuals within breed while the Holstein-Friesian and Jersey populations had the lowest mean heterozygosity (HO =0.370 and 0.376, respectively). The correlation between the genomic-based and pedigree-based inbreeding coefficients was weak ( r =0.171; P <0.001). Mean genomic inbreeding estimates were greatest for Jersey (0.173) and least for Hereford (0.051). The pair-wise breed fixation index ( F st ) ranged from 0.049 (Limousin and Charolais) to 0.165 (Hereford and Jersey). In conclusion, substantial genetic variation exists among breeds commercially used in Ireland. Thus custom-mating strategies would be successful in maximising the exploitation of heterosis in crossbreeding strategies.